Pelatihan Pembuatan Media Pembelajaran Buku Digital Menggunakan Flipbook Pada SDIT Sullamul ‘Ulum - Fauzi Yusa Rahman; Erfan Karyadiputra; Agus Setiawan; Indu Indah Purnomo (ABDINE: Jurnal Pengabdian Masyarakat, 2021)
Learning media is an important part of learning activities. Books are part of learning media that can be displayed following the progress of the times and advances in technology. Teachers play a very important role in learning at school, usually teachers provide material to students using textbooks, whiteboard media or using slides on Microsoft Power Point. In the implementation of this community service activity, training for SDIT Sullamul 'Ulum teachers on how to make digital books using flipbooks, such as using existing tools, making the content in digital books presented interesting so that students are easy to understand and can be applied to Learning Activities. Based on the results of the practice carried out by the participants, it was concluded that the average expertise of 90% of participants could follow and practice in making digital learning media using flipbooks.